2016
DOI: 10.1177/1049731516645665
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a Parenting Program for Low-Income Families in South Africa

Abstract: Objective: This mixed-methods process evaluation examined the feasibility of a parenting program delivered by community facilitators to reduce the risk of child maltreatment in low-income families with children aged 3-8 years in Cape Town, South Africa (N ¼ 68). Method: Quantitative measures included attendance registers, fidelity checklists, satisfaction surveys, and engagement in home practice activities. Qualitative data included parent interviews, facilitator focus groups, and transcripts from parent group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
(60 reference statements)
3
36
0
1
Order By: Relevance
“…There is some evidence suggesting that monitoring implementation can boost its quality. Hence, implementation quality may be lower, if it is not monitored (Lachman et al 2016). For instance, a review of 59 mentoring studies found that programs that monitored implementation had three times higher average effect sizes than programs without monitoring (DuBois et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence suggesting that monitoring implementation can boost its quality. Hence, implementation quality may be lower, if it is not monitored (Lachman et al 2016). For instance, a review of 59 mentoring studies found that programs that monitored implementation had three times higher average effect sizes than programs without monitoring (DuBois et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The program was tested in a pilot RCT, which suggested that although the program had promise, revisions might strengthen its impact and feasibility (Lachman, Cluver, et al., ; Lachman et al., ). Content on positive reinforcement and discipline was subsequently refined, and additional training was provided to facilitators to strengthen competency in the collaborative process and in understanding social learning theory.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the content and structure of each program. PLH for Young Children and PLH for Adolescents provide some of the most promising evidence of parenting program effectiveness in LMICs (Cluver et al, 2018;Cluver et al, 2016;Lachman et al, 2017;Lachman et al, 2018a;Ward et al, 2020). One of the first countries implementing these programs as part of routine service delivery is South Sudan.…”
Section: The Parenting For Lifelong Health Programsmentioning
confidence: 99%